Pendekatan Konseling Behavioral Dalam Menangani Kenakalan Remaja - Fadhil Aryadi; Ati Kusmawati; Desynta Indah Safitri; Muhammad Andri Saputro (Concept: Journal of Social Humanities and Education, 2024)
Juvenile delinquency is deviant behavior carried out by teenagers that violates the law, values ​​and social norms that exist in society, because at this time teenagers are very easy to be influenced by negative things in their environment. Cases of juvenile delinquency in Indonesia have increased from year to year. Reporting from the Indonesian Child Protection Commission (2019) from January to April 2019 there were 37 cases of juvenile delinquency at various levels of education, in 2017 the number was 12.9, increasing to 14 percent in 2018. The aim of the research is to determine the effect of behavioral counseling in dealing with juvenile delinquency so that teenagers can control themselves and not do things that violate social norms in society. This research uses qualitative methods based on post-positivist philosophy, while for the study of natural objects, the researcher is the key tool and data collection techniques are carried out in a combination. Juvenile delinquency is generally caused by personality factors, environmental factors (family, school, community). In this case, behavioral counseling approaches with preventive, curative and coaching efforts can help teenagers control themselves and solve problems. The behavioral counseling approach used in dealing with juvenile delinquency must be carried out optimally based on existing techniques so that it can change and eliminate bad behavior in teenagers.